Orçamento como ferramenta de gestão nas entidades do terceiro setor: um estudo aplicado à instituição educacional superior - Festa, Silvana (2017)
The Third Sector consists on a broad and diverse set of institutions, such as foundations, associations, non-governmental organizations, philanthropic entities, and others, which are private non-profit initiatives and serve to social needs. Thus, this research aims to highlight the use of the financial budget as an essential tool in the effective administration of entity in Third Sector, within the scope of the College Institution. The research used some technical procedures and instruments such as bibliographical and documentary research, analysis and interpretation of literature and study case on a Third Sector entity at the College area. This study is justified due to the transparency and credibility of the institution of at College Education, in addition to assisting it and improving its financial and accounting budget administrative routines. The study concludes that the use of budget as a management tool contributes to the improvement of controls and to an adequate financial management of College Institution, helping the management process and decision making, since the financial resource looks for a better result on the budgeting with the promotion of financial sustainability and guaranteeing the execution of teaching, research and extension policies